Réponses

2013-04-19T16:13:42+02:00

A = 2a * 5

A = 10a

 

B = 6 * 5a

B = 30a

 

C = 4a * 7a

C = 28a²

 

D = (-2a) * (-7a)

D = 14a

 

E = 6a * 7a

E = 42a²

 

F = 3a² * 2a

F = 6a²

 

G = (-2a) * 5a²

G = - 10a²

 

H = -a² * a 

H = -a²

 

I = 2a³ * (-3a)

I = -6a

 

J = 5a² * 3a⁴

J = 15a8

Meilleure réponse !
  • Utilisateur Brainly
2013-04-19T16:15:52+02:00

A = 2a * 5

A = 10a

 

B = 6 * 5a

B = 30a

 

C = 4a * 7a

C = 28a²

 

D = (-2a) * (-7a)

D = 14a

 

E = 6a * 7a

E = 42a²

 

F = 3a² * 2a

F = 6a²

 

G = (-2a) * 5a²

G = - 10a²

 

H = -a² * a 

H = -a²

 

I = 2a³ * (-3a)

I = -6a

 

J = 5a² * 3a⁴

J = 15a8 au carré

 

voilà... :)